2023
DOI: 10.3389/fimmu.2023.1164187
|View full text |Cite
|
Sign up to set email alerts
|

The role of mtDAMPs in the trauma-induced systemic inflammatory response syndrome

Abstract: Systemic inflammatory response syndrome (SIRS) is a non-specific exaggerated defense response caused by infectious or non-infectious stressors such as trauma, burn, surgery, ischemia and reperfusion, and malignancy, which can eventually lead to an uncontrolled inflammatory response. In addition to the early mortality due to the “first hits” after trauma, the trauma-induced SIRS and multiple organ dysfunction syndrome (MODS) are the main reasons for the poor prognosis of trauma patients as “second hits”. Unlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…According to previous studies, mtDNA is released into the joint fluids in rheumatoid arthritis [ 7 ] and released into circulation in trauma [ 10 ], acute respiratory distress syndrome, sepsis, and systemic inflammatory response syndrome, and the increased level of circulating mtDNA is associated with high mortality [ 14 , 17 ]. In this study, we observed a significant positive correlation between cell death and extracellular mtDNA levels, as well as between the extracellular mtDNA and inflammatory cytokine levels in hyperoxia-exposed newborn rat lungs.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, mtDNA is released into the joint fluids in rheumatoid arthritis [ 7 ] and released into circulation in trauma [ 10 ], acute respiratory distress syndrome, sepsis, and systemic inflammatory response syndrome, and the increased level of circulating mtDNA is associated with high mortality [ 14 , 17 ]. In this study, we observed a significant positive correlation between cell death and extracellular mtDNA levels, as well as between the extracellular mtDNA and inflammatory cytokine levels in hyperoxia-exposed newborn rat lungs.…”
Section: Discussionmentioning
confidence: 99%
“…TBI occurs when an external mechanical force impacts the head, leading to temporary or permanent impairments in brain function ( Jenkins, 2023 ). TBI could be of forms, i.e., primary and secondary phases of damages ( Ye et al, 2023 ). The primary injury induced immediately by the external force causes tissue damage through skull fractures, haemorrhages, and vascular injury ( Xiong et al, 2013 ).…”
Section: Role Of Phytochemicals In Tbimentioning
confidence: 99%
“…EGCG also reduces neutrophil infiltration and proinflammatory cytokine production after TBI ( Zeng et al, 2023 ). EGCG remarkably attenuates neuronal apoptosis in the hippocampus induced by TBI by upregulating Bcl-2, downregulating Bax, and cleaved caspase-3 expression ( Ye et al, 2023 ). It also reduces apoptosis by activating the Nrf2 signaling pathway and inducing antioxidant enzymes.…”
Section: Role Of Phytochemicals In Tbimentioning
confidence: 99%